Respiratory Syncytial Virus Increases the Virulence of Streptococcus pneumoniae by Binding to Penicillin Binding Protein 1a. A New Paradigm in Respiratory Infection - Smith, Claire M.; Sandrini, Sara; Datta, Sumit; Freestone, Primrose; Shafeeq, Sulman; Radhakrishnan, Priya; Williams, Gwyneth; Glenn, Sarah M.; Kuipers, Oscar P.; Hirst, Robert A.; Easton, Andrew J.; Andrew, Peter W.; et al. (American journal of respiratory and critical care medicine, 2014)
Respiratory syncytial virus (RSV) and Streptococcus pneumoniae are major respiratory pathogens. Coinfection with RSV and S. pneumoniae is associated with severe and often fatal pneumonia but the molecular basis for this remains unclear. To determine if interaction between RSV and pneumococci enhances pneumococcal virulence. We used confocal microscopy and Western blot to identify the receptors involved in direct binding of RSV and pneumococci, the effects of which were studied in both in vivo and in vitro models of infection. Human ciliated respiratory epithelial cell cultures were infected with RSV for 72 hours and then challenged with pneumococci. Pneumococci were collected after 2 hours exposure and changes in gene expression determined using quantitative real-time polymerase chain reaction. Following incubation with RSV or purified G protein, pneumococci demonstrated a significant increase in the inflammatory response and bacterial adherence to human ciliated epithelial cultures and markedly increased virulence in a pneumonia model in mice. This was associated with extensive changes in the pneumococcal transcriptome and significant up-regulation in the expression of key pneumococcal virulence genes, including the gene for the pneumococcal toxin, pneumolysin. We show that mechanistically this is caused by RSV G glycoprotein binding penicillin binding protein 1a. The direct interaction between a respiratory virus protein and the pneumococcus resulting in increased bacterial virulence and worsening disease outcome is a new paradigm in respiratory infection.